ナンキョク セイソウケン ノ チッソ サンカブツ ノ カガク - 近藤, 豊; コンドウ, ユタカ; 小池, 真; コイケ, マコト; Kondo, Yutaka; Koike, Makoto (1997)
P(論文) 南極の春先に成層圏オゾンが減少する"オゾンホール"の形成において, 窒素酸化物の季節変化は重要な役割を果たしている。オゾンを破壊する塩素酸化物(Cl, ClOなど)は, 二酸化窒素(NO_2)と反応するとオゾンを直接破壊しない準安定物質であるClONO_2に変換されてしまう。このため冬から春先へかけてのNO_2の不活性化(HNO_3への変換)と, HNO_3を取り込んだ極成層圏雲(PSCs)の重力落下による窒素酸化物の成層圏からの除去過程(脱窒denitrification)がオゾンホール出現のために不可欠な条件となっている。このような窒素酸化物の季節変化を調べるために, 成層圏NO_2の連続観測を南極昭和基地において1990年3月より可視分光器を使って始めた。この結果, 夏に極大, 冬に極小が現れ, 春先にはNO_2の不活性化と脱窒により増加が遅い明瞭な季節変化が得られた。この春先のNO_2のゆっくりとした増加は, PSCs上での不均一反応を取り入れたモデル計算と良く一致した。これらの結果は, オゾンホール中でのオゾンの減少を定量的に理解する上で鍵となるNO_2量を, 観測から明かにし, モデルの中で再現できる事を確かめたという点で重要である。一方, 1991年の年末の極渦の崩壊から1992年初めの秋にかけては, ピナツボ火山噴火によって増大した硫酸エーロゾル上での不均一反応により, NO_2が30%ぐらい減少した結果が得られた。この不均一反応は夜間に生成するN_2O_5を必要とするため, 一日中光のあたる南極の夏におけるNO_2の減少は, 中緯度においてNO_2が既に減少した空気が輸送されてきた結果と考えられる。 Low levels of reactive nitrogen species are essential for large stratospheric ozone (O_3) depletion over the Antarctic continent in the austral spring (Antarctic ozone hole), because ClO is sequestered by a reaction with NO_2 to form a quasi-stable molecule ClONO_2. The column amounts of NO_2 have been measured using a visible spectrometer at Syowa Station, Antarctica (69°S) since March 1990. The NO_2 column exhibits a large seasonal variation with a maximum in summer and a minimum in winter. The recovery of NO_2 in spring is 2-3 times slower than the fall decay. The low NO_2 level in mid-winter to early spring is considered to be due to a conversion into HNO_3 on PSCs and due to the denitrification by gravitational sedimentation of PSC particles. Results from a chemical box model agreed well with this slow rate of NO_2 increase in spring when heterogeneous chemistry on PSCs was included. The reduction of NO_2 by 30% was found after the breakup of the austral polar vortex in 1992. This is probably due to the transport of air from lower latitudes, where NO_2 is reduced by heterogeneous conversion into HNO_3 on the surface of sulfate aerosols increased by the Pinatubo volcanic eruption. departmental bulletin paper